2009
DOI: 10.1088/1464-4258/11/5/054012
|View full text |Cite
|
Sign up to set email alerts
|

Growth variation effects in SiGe-based quantum cascade lasers

Abstract: Abstract. Epitaxial growth of SiGe quantum cascade (QC) lasers has thus far proved difficult, and nonabrupt Ge profiles are known to exist. We model the resulting barrier degradation by simulating annealing in pairs of quantum wells (QWs). Using a semiclassical charge transport model, we calculate the changes in scattering rates and transition energy between the lowest pair of subbands.We compare results for each of the possible material configurations for SiGe QC lasers. The effects are most severe in n-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This system has a far lower effective mass of about which is crucial to not only improving the gain through higher wavefunction overlap and matrix elements, but also as lower effective masses improve the tolerance of subband alignment to growth inaccuracies [108]. Indeed Valavanis et al [108] have used the diffusion profiles measured by TEM [122] to provide more accurate modelling of the subband positions due to rounding of the heterostructure barrier profiles from Ge segregation and diffusion. A number of designs have been suggested with Ge quantum wells with gain well above the waveguide losses not only at 4 K but also at room temperature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This system has a far lower effective mass of about which is crucial to not only improving the gain through higher wavefunction overlap and matrix elements, but also as lower effective masses improve the tolerance of subband alignment to growth inaccuracies [108]. Indeed Valavanis et al [108] have used the diffusion profiles measured by TEM [122] to provide more accurate modelling of the subband positions due to rounding of the heterostructure barrier profiles from Ge segregation and diffusion. A number of designs have been suggested with Ge quantum wells with gain well above the waveguide losses not only at 4 K but also at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…This was due to the growth not being accurate enough to provide alignment between the subband states in the injector at any electric field. The effect of growth variations has been studied by Valavanis who has shown that for such LH to HH structures to align, the heterolayer thickness requires to be within 1 monolayer and the Ge content must be accurate to within better than 1 part in 10 3 [108]. The present growth tools are not yet capable of meeting these tolerance requirements unless a significant number of calibration samples are used to accurately set the growth parameters.…”
Section: Voltage (V)mentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 This leads to significant changes in the bandstructure and scattering lifetimes, 46,47 and can therefore degrade the performance of devices. In this section, we investigate the impact of interdiffusion on the QCL gain and we attempt to recover the lost performance through design optimization.…”
Section: B Interdiffusion Compensationmentioning
confidence: 99%
“…Clearly a move to electron based QCL designs which could use the more parabolic conduction bands would not only make the characterization of spontaneous emission easier but should also show significantly higher gain mainly through the lighter m ‫ء‬ , according to a number of proposals. [36][37][38] Further work has also determined that lighter m ‫ء‬ systems such as n-type Ge quantum well QCLs have more tolerance to growth fluctuations and inaccuracies 38 and a number of multiple Ge quantum well heterostructures have now been demonstrated experimentally. [39][40][41][42][43] The present designs have also suffered by the upper radiative state not being inside the energy range of the miniband thereby reducing the coupling between the injector and the upper radiative state.…”
mentioning
confidence: 99%